Gambaran Tingkat Pengetahuan Swamedikasi Demam pada Balita di Posyandu Desa Karanganyar Kecamatan Tamansari Kabupaten Boyolali - Ahmad Fatah Bisri; Hanugrah Ardya; Joko Santoso (An-Najat, 2024)
Fever is a condition where the body temperature is above the normal temperature limit, namely ≥ 38°C. If fever is not treated immediately, seizures can occur in toddlers which endangers the toddler's safety. In Indonesia, it was reported that the incidence of febrile seizures was 3-5% of children aged 5-6 months in 2017-2018. This figure continues to increase to 6% in 2019. Fever is one of the symptoms that can be treated with self-medication. The Indonesian Ministry of Health explains that self-medication is a person's attempt to treat the symptoms of a disease without consulting a doctor. The aim of this study was to determine the level of knowledge about fever self-medication among toddlers at posyandu. This research method is descriptive. The sample in this study was mothers of toddlers who were active members of the posyandu with a total of 93 respondents. Sample selection used purposive sampling. The instrument in this research used a questionnaire distributed to 93 respondents. The results of this study show that of the 93 respondents with characteristics aged 26-30 years 69.9%, high school education 86.0%, private employment 80.6% and the level of knowledge of fever self-medication at posyandu in the good category 86.0%, moderate category 11.8% and the less than 2.2% category. The conclusion is that the level of knowledge about fever self-medication in toddlers at the posyandu in Karanganyar Village, Tamansari District, Boyolali Regency is included in the good category, namely 86.0%.